Partycypacja obywatelska na poziomie lokalnym - Tybuchowska-Hartińska, Karolina (Political Preferences, 2012)
The main way of citizen's participation are elections. Elections at local level, espe- cially to local government, are very important for contemporary democracy. The key issue for developing democracy is activity of citizens which is very often called as civil society. Hence, the aim of the article is to find what is the citizen's participation at local level.The most popular form of activity at local level are: inhabitant consultation; country meeting; district meeting; local referendum. Supporters of SLD (39% of them) declared par- ticipation in country meetings. In other parties this indicator was at lower level, for example in PSL (33,3%) and PiS (28%). It looks different when the question is related to participation in an inhabitant consultation. In this case, the majority of supporters of PO (29,6%) take part in this kind of activity. Similar percents are in Ruch Palikota (29,6%) and PSL (29,3%). Sup- porters of PiS (28,8%) and PO (27,8%) attend actively in local referendum.To sum up, we can conclude that the participation at local level is not very optimistic or pessimistic. Unfortunately, we are not able to indicate clear conclusions, but only find some helpful notes for a further research. Presented study allows us to find many positive aspects and encourage us to continue this subject.